Transformational Leadership, Career Adaptability, and Work Behaviors: The Moderating Role of Task Variety - Lan, Yujuan; Chen, Zhixia (Frontiers in Psychology, 2020)
Career adaptability is a set of individual resources that benefit one’s sustainable development in his/her life-long careers, especially in today’s turbulent environment. However, how to foster employees’ career adaptability through managerial strategies and eventually contribute to the organizations remains to be studied. Guided by the career construction theory, we posit a moderated mediation model that transformational leadership (TFL) could strengthen employees’ career adaptability and further foster their task performance and organization-directed citizenship behavior (OCBO), with task variety moderating the mediation effect. We conducted a three-wave survey with 558 supervisor-employee dyads to test the overall model. The results validated that career adaptability mediated the links between TFL and task performance as well as OCBO. Furthermore, the mediation effect was stronger for employees who had higher level of task variety. In short, our study offers the groundwork to understand that employees’ career adaptability can be activated by transformational leaders and is self-regulatory to benefit work behaviors in the task variety context. It enlightens organizations to cultivate employees’ career adaptability in the way of TFL and job design, with the objective of promoting the sustainable development for both the employees and the organizations.